Development of a novel protocol for the permanent hydrophilic modification of a BOPP film for high quality printing with water-based ink. Issue 107 (16th October 2015) - Chen, W. X.; Yu, J. S.; Chen, G. L.; Qiu, X. P.; Hu, W.; Bai, H. Y.; Shao, J. Z.
Abstract : This paper reports the successful modification of biaxially oriented polypropylene (BOPP) films to permanently enhance their hydrophilic properties for potential flexible packing applications. Abstract : This paper reports the successful modification of biaxially oriented polypropylene (BOPP) films to permanently enhance their hydrophilic properties for potential flexible packing applications. This protocol consists of three sequential processes: (1) an on-line dielectric barrier discharge (DBD) plasma pretreatment, (2) a polyvinyl alcohol/silk fibroin/polyethylene glycol (PVA/SF/PEG) coating, and (3) ethanol solution finishing. The optimal modification conditions included: DBD plasma pretreatment for 10 seconds, coating with aqueous PVA/SF/PEG (3%/3%/1%) solution, and finally, 8 minutes of treatment with 60% ethanol solution. The fully modified BOPP films exhibited approximately a 16° static contact angle (SCA), a near zero haze value, and an effectively 100% transmittance value under visible light (400–700 nm). Atomic force microscopy (AFM) images of the surface morphology of the modified BOPP films showed that the surface roughness increased from 3.79 nm (untreated) to 21.10 nm (fully treated). The Fourier transfer infrared spectroscopy (FT-IR) results showed that polar functional CO groups were grafted onto the BOPP film that was pretreated with the DBD plasma. Further modification of the pretreated BOPP film with the PVA/SF/PEG coating significantly enhanced the density of the C–O and N–H groups. The gravure printing images indicated that the adhesive property of the BOPP film for water-based ink improved substantially after the hydrophilic modifications.